PENGUATAN TUGAS DAN FUNGSI PENGAJAR PELAYAN ANAK DAN REMAJA DI KLASIS LOBALAIN - Luji , Daud Saleh; Tari, Ezra; Pairikas, Fenetson (CV. Alina, 2023)
The aim of community service activities is related to explaining the duties and functions of teachers. Strengthening the roles and responsibilities of teachers serving children and adolescents is a crucial action in ensuring the continuity of their education and optimal development. Teachers are still hampered by a lack of tools and understanding of teaching creativity. Methods for implementing services, discussing and practicing. Interact with children to convey the goals and themes in storytelling activities. From the results of community service activities, it can be concluded that generally they are able to implement pop up books with puppet shows on stage. The teacher reveals about story development. The teacher emphasizes communication strategies that can affect children's emotions.